2019
DOI: 10.1002/em.22341
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes and Y chromosome instability in radiation‐exposed male workers in cardiac catheterization laboratory

Abstract: Occupational radiation exposure may impact the reproductive outcome of male workers in the cardiac catheterization laboratory (cath Lab) who receive a dose of ~1–10 mSv/year. An increased copy number variation (CNV) in azoospermia factor region c (AZFc) of the Y chromosome is a marker of spermatogenic failure, previously associated with radiation exposure. This study sought to investigate the association between paternal exposure in the Cath Lab and adverse reproductive outcomes as well as to assess the induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
1
10
0
1
Order By: Relevance
“…Similar trends were described by M.G. Andreassi with colleagues [7] when they assessed influence exerted by occupational exposure on reproductive outcomes among personnel working at a heart catheterization laboratory and exposed to an annual dose equal to 1-10 mSv/year. They showed that chronic occupational exposure of male workers correlated with higher prevalence of low birthweight among their offspring (OR = 2.7, CI 1.1-6.3).…”
supporting
confidence: 78%
“…Similar trends were described by M.G. Andreassi with colleagues [7] when they assessed influence exerted by occupational exposure on reproductive outcomes among personnel working at a heart catheterization laboratory and exposed to an annual dose equal to 1-10 mSv/year. They showed that chronic occupational exposure of male workers correlated with higher prevalence of low birthweight among their offspring (OR = 2.7, CI 1.1-6.3).…”
supporting
confidence: 78%
“…The latter exposure parameter takes into account the number of years in catheterization laboratory, the number of procedures per year, and the distance from the source of radiation. Recently, using quantitative real-time PCR, a significantly higher rate of microdeletion and microduplication as assessed by copy number variation (CNV) in the SY1197 sequence-tagged site of the Y-chromosome azoospermia factor region c (AZFc) was shown in male Cath lab workers compared to unexposed controls (CNV = 1.53 ± 0.8 vs. CNV = 1.02 ± 0.4 respectively, p = 0.0005) [ 29 ]. However, a non-significant difference was shown for the SY579 site CNV in AZFc region between exposed and unexposed workers.…”
Section: Resultsmentioning
confidence: 99%
“…There were six studies that investigated occupational exposure from medical ( n = 3) (Andreassi et al 2020 ; Fucic et al 2008 ; Lawson et al 2012 ), nuclear ( n = 2) (Doyle et al 2000 ; Parker et al 1999 ), and flight attendant ( n = 1) (Grajewski et al 2015 ) sectors. A total of 14 studies examined medical exposures for diagnostic ( n = 6) (Chen et al 2018 ; Choi et al 2013 ; Goldberg et al 1997 ; Guilbaud et al 2019 ; Hujoel et al 2004 ; Mortazavi et al 2013 ) or therapeutic ( n = 8) (Chiarelli et al 2000 ; Green et al 2010 ; Green et al 2002 ; Källén et al 1998 ; Reulen et al 2009 ; Signorello et al 2006 ; van de Loo et al 2019 ; Winther et al 2008 ) purposes.…”
Section: Resultsmentioning
confidence: 99%